1999
DOI: 10.1128/iai.67.8.4014-4018.1999
|View full text |Cite
|
Sign up to set email alerts
|

New Exfoliative Toxin Produced by a Plasmid-Carrying Strain of Staphylococcus hyicus

Abstract: A new serotype of Staphylococcus hyicus exfoliative toxin (SHET), serotype B, was isolated from the culture filtrate of a plasmid-carrying strain of S. hyicus. The new SHET was purified by precipitation with 70% saturated ammonium sulfate, gel filtration on a Sephadex G-75 column, column chromatography on DEAE–Cellulofine A-500, and sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). The new SHET caused exfoliation of the epidermis as determined by the so-called Nikolsky sign when inoculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 27 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…In Staphylococcus hyicus, five isoforms of ETs (SHETB, ExhA, ExhB, ExhC and ExhD) have been reported, whose amino acid sequences are homologous to those of S. aureus ETs (Sato et al, 1999;Ahrens & Andresen, 2004). Among the five isoforms of S. hyicus ETs, the four Exh isoforms were primarily isolated from S. hyicus causing exudative epidermitis in pigs (Futagawa-Saito et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In Staphylococcus hyicus, five isoforms of ETs (SHETB, ExhA, ExhB, ExhC and ExhD) have been reported, whose amino acid sequences are homologous to those of S. aureus ETs (Sato et al, 1999;Ahrens & Andresen, 2004). Among the five isoforms of S. hyicus ETs, the four Exh isoforms were primarily isolated from S. hyicus causing exudative epidermitis in pigs (Futagawa-Saito et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Two toxins isolated in Japan were designated SHETA and SHETB, 15,16 whereas four toxins isolated in Denmark were designated ExhA, ExhB, ExhC and ExhD 4,17,18 . Previous studies demonstrated that injection of both Japanese isolates to 1‐day old chickens resulted in skin exfoliation, and that the inoculation of SHET‐producing strains of S. hyicus into piglets caused skin lesions similar to EE 5,19,20 . Deduced amino acid sequence analysis revealed that all four isoforms of Exh as well as SHETB show amino acid sequence similarity with ETA, ETB and ETD, including those in the active site of serine proteases.…”
Section: Introductionmentioning
confidence: 99%
“…ETB is found on plasmids that vary in size from approximately 35 to 60 kilobases, yet the genetic organization of these plasmids appears to be conserved ( Figure 2B) (48). Interestingly, the exfoliative toxins of Staphylococcus hycius, SHETA and SHETB, which are associated with exudative epidermitis in pigs and chickens, are similar to ETA and ETB -SHETA is produced by plasmid-free strains, while SHETB production is dependent on the presence of a large plasmid (49,50).…”
Section: Exfoliative Toxinmentioning
confidence: 99%